Developing real-time face mask detection with facial temperature measure for Covid-19 indoor monitoring system - Aharari, Ari; Abe, Jair Minoro; Nakamatsu, Kazumi (Journal of Computer Science and Cybernetics, 2021)
The coronavirus (COVID-19) is the latest pandemic that hit human health in 2019. Wear a face mask in public areas to decrease the spread of the coronavirus. This work presents real-time face mask detection with facial temperature measures for the COVID-19 indoor monitoring system. Detecting people using ultrasonic sensors, face mask detection, and facial temperature measure using Grid-Eye Sensor are three modules applied in the proposed system. We also evaluated the proposed monitoring system in the real environment and confirmed the accuracy of 98.8% of mask detection.